DIGITAL MARKETING STRATEGY TO SURVIVE DURING COVID-19 PANDEMIC - Ayu Mirah Anjasmara Putri; I Gede Sanica (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Indonesia is currently experiencing the spread of the Covid-19 virus, which has not subsided. The government's appeal to prevent the spread of this virus requires the public to stay at home. Uncertainty during the COVID-19 pandemic has resulted in business actors, one of which is the Coffee Shop, which has experienced a decline in income. For this reason, coffee shops must have a strategy to survive during the COVID-19 pandemic. Digital marketing strategy is a form of business to promote and introduce a brand and product using digital media. It is the right step to survive during this pandemic. This study aims to find out how to apply digital marketing strategies to BC Street Coffee to be able to survive during the covid-19 pandemic. This study uses a qualitative method by selecting a case study on BC Street Coffee through interviews and documentation to the intended informants. Informants in this study were owners, employees, and customers. Based on the results of the interview, BC Street Coffee implemented a digital marketing strategy to survive during the covid-19 pandemic with several strategies, namely 1) Implementing social media marketing, BC Street Coffee used Instagram and Facebook as marketing media by utilizing photo and video features to disseminate information about BC Street Coffee and promos that apply to the delivery application (GoFood & GrabFood) consumers so they can find out the products offered by BC Street Coffee, 2) Implement content marketing, BC Street Coffee uses marketing content to help introduce products through features- features adopted from social media, using messages that are packaged creatively using attractive photos, captions, hashtags, and videos. And BC Street Coffee uses or collaborates with local influencers in marketing or introducing products.